Making Waves: Marine Citizen Science for Impact - Schläppy, Marie-Lise; Loder, Jennifer; Salmond, Jodi; Lea, Alexandra; Dean, Angela J.; Roelfsema, Chris M. (Frontiers in Marine Science, 2017)
The benefit of engaging volunteers in marine citizen science projects goes beyond generation of data and has intrinsic value with regards to community capacity-building and education. Yet, despite the documented benefits of citizen science, there can be barriers to the process of developing strategic citizen science projects and translating data into valued results with natural resource management applications. This paper presents four case-studies from fifteen years of Reef Check Australia (RCA) marine citizen science research and education projects. These case studies convey approaches and lessons-learned from the process of designing, implementing and sharing citizen science programs with the goal to create valuable social and environmental outcomes: 1) Demonstrating citizen science data quality through a precision study on data and analysis of 15 years of standardized Reef Check (RC) reef health data in Queensland, Australia. 2) Identifying and responding to data gaps through volunteer monitoring of sub-tropical rocky reefs in South East Queensland, Australia. 3) Adapting citizen science protocols to enhance capacity building, partnerships and strategic natural resource management applications through reef habitat mapping. 4) Tailoring new pathways for sharing citizen science findings and engaging volunteers with the community via a Reef Check Australia Ambassadors community outreach program. These case studies offer insights into considerations for developing targeted and flexible citizen science projects, showcasing the work of volunteers and project stakeholders, and collaborating with partners for applications beneficial to research, management and education.